A Simulation Analysis of the Effects of Population Change on a Neoclassical Economy - Denton, Frank T.; Spencer, Byron G. (Journal of Political Economy, 1973)
This paper is concerned with the effects of variations in demographic factors on the time paths of major economic variables. A theoretical macromodel of an economic-demographic system is specified, with numerical parameters. This model is used in computer simulations to study the economic effects of exogenous changes in fertility and immigration rates. A cohort approach is emphasized in the specification of both demographic and economic relationships. Simulation results are reported for a variety of real and artificial time patterns of fertility and immigration under different assumptions about the values of the principal parameters of the economic relationships.